Cytological Effects of Leaf Extract of Artemisia vulgaris L. on Meristematic Cells of Allium cepa L. - Rai, P.D.; Paudel, N.; Shakya, S.R. (Our Nature, 2013)
Artemisia vulgaris L., a perennial aromatic shrub with bitter taste, is considered as a medicinal plant and water extract of it consists of active components like psilostachyin A, psilostachy C, Exiguaflavanone A, Maackiain, fernenol with both anti-bacterial and medicinal value. It has been used to perserve crops and stored grains both in liquid and powder by farmers. The cytological effect was observed in 5, 7.5, 10 and 20% concentrations of Leaf Extract of Artemisia vulgaris (LEA) on Allium cepa L. in five different time durations. The present study showed the correlation between concentration of LEA and duration of treatment in controlled state. Higher concentrations of LEA as well as longer duration of treatment generate the inhibitory effect on the division of cells. Lower concentration of LEA showed less effect on Mitotic Index value (MI) in comparison with control value, which is attributed to delay in metabolic activities. It also showed the change in phase indices and induced chromosomal abnormalities among the phases. DOI: http://dx.doi.org/10.3126/on.v10i1.7787